Digital Competence, Knowledge Sharing, and Innovative Work Behavior: The Role of Absorptive Capacity - Wachyu Hari Haji (SEAN Institute, 2026)
Digitalization has changed the way employees perform, communicate, and develop new work practices, particularly in higher education institutions and service organizations that increasingly rely on digital systems. However, digital competence and knowledge sharing may not automatically lead to innovative work behavior unless employees are able to absorb, process, and apply new knowledge. This study aims to analyze the effects of digital competence and knowledge sharing on innovative work behavior, both directly and through absorptive capacity as a mediating variable. This study employed a quantitative explanatory approach. Data were collected through a structured questionnaire using a five-point Likert scale from 254 employees working in higher education institutions and digitalized service organizations. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model met the required validity and reliability criteria, with all outer loadings above 0.70, AVE values above 0.50, and composite reliability and Cronbach’s alpha values above 0.70. The structural model showed that digital competence and knowledge sharing had positive effects on absorptive capacity, while absorptive capacity had a positive effect on innovative work behavior. However, the direct effects of digital competence and knowledge sharing on innovative work behavior were not significant. The specific indirect effects confirmed that absorptive capacity fully mediated both relationships. These findings indicate that innovative work behavior is not formed merely through digital skills or knowledge exchange, but through employees’ ability to absorb and apply knowledge in their work.